1989
DOI: 10.1038/jcbfm.1989.21
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Effects of Mild Hypothermia on Global Cerebral Ischemia and Recirculation in the Cat: Comparison to Normothermia and Hyperthermia

Abstract: Summary:The metabolic effects of graded whole body hypothermia on complete global cerebral ischemia and recirculation was investigated in the cat. Hypothermia was induced to one of three levels prior to ischemia; T = 26.8° ± OSC (n = 4), T = 32.1° ± 0.2°C (n = 5), and T = 34.6° ± 0.3°C (n = 6), and maintained constant throughout 16 min of ischemia and 1.5-2 h of recircula tion. Intracellular cerebral pH and relative concentrations of high-energy phosphate metabolites were continuously monitored, using in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(77 citation statements)
references
References 44 publications
4
70
1
2
Order By: Relevance
“…temperature reductions of 4°C were associated with higher brain ATP concentration initially during ischemia, but by the end of the ischemic interval were similar to values of normothermic controls (8,9). In our laboratory, an intraischemic temperature difference of 2.9"C between normothermic and modestly hypothermic piglets was associated with a trend for greater preservation of brain ATP in cooler animals (57 versus 43% of control for hypothermic versus normothermic, p = 0.11) (4).…”
Section: Laptook Et Alsupporting
confidence: 57%
See 1 more Smart Citation
“…temperature reductions of 4°C were associated with higher brain ATP concentration initially during ischemia, but by the end of the ischemic interval were similar to values of normothermic controls (8,9). In our laboratory, an intraischemic temperature difference of 2.9"C between normothermic and modestly hypothermic piglets was associated with a trend for greater preservation of brain ATP in cooler animals (57 versus 43% of control for hypothermic versus normothermic, p = 0.11) (4).…”
Section: Laptook Et Alsupporting
confidence: 57%
“…However, the effect of a modest reduction in temperature (2-3°C) on such variables has not been examined and cannot be extrapolated from these reports due to the absence of results at temperatures between 25 and 38°C. This issue is further clouded by the report of Chopp et al (8) in which the extent of change in phosphorylated metabolites during a fixed time interval of ischemia, as determined using 3 1~ MRS in adult cats, was independent of temperature over the range of 26.8-34.6"C. What has been examined is the effect of temperature on brain metabolic rate, using CMRo, as an index of metabolic activity. All studies in neonates and adults agree that a reduction in core body or brain temperature is associated with a lowering of CMRo,, but the magnitude of reduction in CMRo, for a given decrease in temperature remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia can target more than one aspect of secondary brain injury, including oxygen consumption and metabolic demand, 15 enzymatic degradation, neurotransmitter uptake, 7 membrane stabilization, and reduction in intracellular acidosis. 32,55 In a small study, hypothermia post-middle cerebral artery (MCA) stroke has been shown to be tolerable, help control intracranial pressure, and possibly lead to better neurological outcomes.…”
Section: Hypothermiamentioning
confidence: 99%
“…A reduction of cerebral oxygen consumption has been proposed (Hegnauer et al 1954) and other multifactorial physical and chemical mechanisms during and after low-flow induced ischaemia have also been postulated (Hypothermia after Cardiac Arrest Study Group 2002). These include reduction of intracellular acidosis (Chopp et al 1989), reducing cerebral oedema and protection of lipoprotein membranes (Dempsey et al 1987), inhibition of biosynthesis and release of excitatory neurotransmitters (Busto et al 1989). ATP concentration in brain tissue has been shown to most consistently reflect biochemical activity among available biochemical indicators.…”
Section: Hypothermia After Cardiac Arrestmentioning
confidence: 99%